2017
DOI: 10.1007/s10265-017-0919-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of slope on Spartium junceum root system: morphological, anatomical and biomechanical adaptation

Abstract: Root systems have a pivotal role in plant anchorage and their mechanical interactions with the soil may contribute to soil reinforcement and stabilization of slide-prone slopes. In order to understand the responses of root system to mechanical stress induced by slope, samples of Spartium junceum L., growing in slope and in plane natural conditions, were compared in their morphology, biomechanical properties and anatomical features. Soils sampled in slope and plane revealed similar characteristics, with the exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
5
13
1
Order By: Relevance
“…RAR trends for shrub and tree profiles in our study can be compared with previous results [63]. Lombardi et al [62] found that the number of fine roots of Spartium junceum L. was highest in the upper 10 cm and decreased with soil depth. In our study, RAR values were generally higher compared to the values obtained in other Mediterranean and alpine sites [27,41], except for values of chestnut, which are comparable with the results obtained by Bischetti et al [41].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…RAR trends for shrub and tree profiles in our study can be compared with previous results [63]. Lombardi et al [62] found that the number of fine roots of Spartium junceum L. was highest in the upper 10 cm and decreased with soil depth. In our study, RAR values were generally higher compared to the values obtained in other Mediterranean and alpine sites [27,41], except for values of chestnut, which are comparable with the results obtained by Bischetti et al [41].…”
Section: Discussionsupporting
confidence: 81%
“…For woody shrubs, RAR values were very similar for all four species, while the largest number of roots were present in the 10 to 20 cm soil depth interval. Significantly, because of our mountainous site, more lateral roots were located below the upper 10 cm soil depth; plants growing on relatively flat sites typically have more abundant lateral roots in the upper 10 cm of soil compared to hillslopes [62]. RAR trends for shrub and tree profiles in our study can be compared with previous results [63].…”
Section: Discussionsupporting
confidence: 52%
“…The importance of parent material is especially relevant on bare soils devoid of protective vegetation cover such as in recently afforested areas and planted orchards (Corti et al 2011). The lack of vegetation allows the parent material to be a driving factor of soil erosion (Atucha et al 2013;Lombardi et al 2017). This is very relevant in agricultural land such as vineyards, where the lack of vegetation due to tillage and the use of herbicides results in high erosion rates that are dependent on the parent material type.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of rootless substrate decreases by the heat action of the loosely bound water. EPS particles improve the heat preservation performance of substrate, but the heat preservation performance of substrate degrades with the growth of plants.roots grow, it would provide anchoring into bedrock or stable soil layers, which would be further favorable for the slope stability [12][13][14].Due to the high production efficiency, soil-spraying technology, which was first developed by Japanese scholars [15], has been widely used in vegetation engineering for slope restoration. Nevertheless, it was reported that it is difficult to facilitate vegetation on the steep slopes [16].…”
mentioning
confidence: 99%
“…roots grow, it would provide anchoring into bedrock or stable soil layers, which would be further favorable for the slope stability [12][13][14].…”
mentioning
confidence: 99%